A protectionist bias in majoritarian politics - Grossman, Gene M. 1955-; Helpman, Elhanan 1946- (National Bureau of Economic Research, 2004)
"We develop a novel model of campaigns, elections, and policymaking in which the ex ante objectives of national party leaders differ from the ex post objectives of elected legislators. This generates a distinction between "policy rhetoric" and "policy reality" and introduces an important role for "party discipline" in the policymaking process. We identify a protectionist bias in majoritarian politics. When trade policy is chosen by the majority delegation and legislators in the minority have limited means to influence choices, the parties announce trade policies that favor specific factors, and the expected tariff or export subsidy is positive. Positions and expected outcomes monotonically approach free trade as party discipline strengthens"--National Bureau of Economic Research web site.
Keywords: Politik; Wirtschaftspolitik; Economic policy -- Political aspects; Protectionism -- Political aspects